HOW DOES CLINICAL LEARNING ENVIRONMENT CHANGES DURING PANDEMIC AFFECT ON PROFESSIONAL IDENTITY? - Yoga Pamungkas Susani; Dian Puspita Sari; Emmy Amalia (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2022)
Background: The COVID-19 pandemic has disrupted clinical medical education, and clinical learning was forced to swiftly adapt by blending offline clinical services with online learning. Changes in the clinical learning environment will have an impact on professional identity. This study aimed to determine the impact of changes in the learning environment on medical students' professional identity. Methods: This was a two-phase mixed-method study with an explanatory sequential design. The PHEEM instrument measured students' perceptions of the learning environment before and during the pandemic, and PIM was used to measure professional identity. Fifty-one clinical students participated in this phase. In the second qualitative phase, fifteen students were selected to join three focus group discussions based on the proportion of sex and completion of the clinical rotation.Results: there was a significant decrease in student perceptions of teaching during the pandemic (p 0.003). This result is in line with qualitative findings, namely a decrease in opportunities for participation and interaction in the social aspects of learning. This lowered self-confidence in clinical competence was supported by a higher correlation between perceptions of the learning environment and professional identity before the pandemic than during the pandemic (respectively r 0.561; 0.554 p < 0.01).Conclusion: During the pandemic, there was a decrease in clinical students' participation opportunities, which resulted in decreased confidence in specific clinical competencies, but decreased participation had no effect on comfort and willingness to be engaged in the medical profession. This situation brings awareness to further improve competence through various training and practices.